Add to cart the impact of COVID-19 government stringency measures on e-commerce sales - Ma, Audrey Reiko S.; Villadolid, Leland Alfonso S.
This paper investigates the effect of stringency on the growth of e-commerce sales in Australia, Canada, South Korea, the United States, and the United Kingdom at the height of the COVID-19 pandemic. We ran pooled ordinary least squares regressions using monthly data from March 2020 to December 2021, which covers the onset and the exponential rise of COVID-19 cases during the first two years of the pandemic. The results show that stringency has a lagged positive effect on e-commerce, indicating that stricter government containment measures encouraged more consumers and sellers to shift to e-commerce platforms at the height of the lockdowns. This is consistent with the technological acceptance framework which suggests that stringency increased the perceived usefulness of e-commerce since it provided a safe alternative that allowed consumers and firms to perform economic transactions without violating the government’s containment measures.